2003
DOI: 10.1016/s0020-0190(03)00261-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal one-page tree embeddings in linear time

Abstract: In the minimum linear arrangement problem one wishes to assign distinct integers to the vertices of a given graph so that the sum of the differences (in absolute value) across the edges of the graph is minimized. This problem is known to be NP-complete for the class of all graphs, but polynomial for trees-algorithms of time complexity O(n 2.2 ) and O(n 1.6 ) were given by Shiloach [SIAM J. Comput. 8 (1979) 15-32] and Chung [Comput. Math. Appl. 10 (1984) 43-60], respectively. We present a linear-time algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…In this example, A has two dependents, and minimal dependency length is achieved by placing these two dependents on opposite sides of the head. This prediction of DLM was derived by Gildea & Temperley (2007, and presaged by work on similar problems in abstract graph theory (Hochberg & Stallmann 2003). Gildea & Temperley (2007) found that the optimal strategy to achieve minimal dependency length (while maintaining projectivity) is to place dependents on alternating sides of their head outward in order of increasing length.…”
Section: Short-before-long and Long-before-short Constituent Ordering...mentioning
confidence: 93%
See 1 more Smart Citation
“…In this example, A has two dependents, and minimal dependency length is achieved by placing these two dependents on opposite sides of the head. This prediction of DLM was derived by Gildea & Temperley (2007, and presaged by work on similar problems in abstract graph theory (Hochberg & Stallmann 2003). Gildea & Temperley (2007) found that the optimal strategy to achieve minimal dependency length (while maintaining projectivity) is to place dependents on alternating sides of their head outward in order of increasing length.…”
Section: Short-before-long and Long-before-short Constituent Ordering...mentioning
confidence: 93%
“…While DLM favors projective word orders, it is not the case that minimal-dependency-length word orders are necessarily projective. It is in some cases possible to achieve lower dependency lengths by breaking projectivity (Chung 1984;Hochberg & Stallmann 2003;Park & Levy 2009).…”
Section: What Can Dependency Locality Explain?mentioning
confidence: 99%
“…reduces crossings to practically zero [7], this does not provide a full explanation about the low frequency of crossings in real sentences: (a) minimum D does not imply C = 0 [11], (b) the actual value of D in real sentences is located between the minimum and that of a random ordering of vertices [12] and (c) the word order that minimizes D might be in a serious conflict with other linguistic or cognitive constraints [13]. Here the problem of the reduction of D that is required for explaining C ≈ 0 in real sentences is avoided by means of a null hypothesis that predicts C by considering the actual length of the edges that may cross.…”
mentioning
confidence: 99%
“…It has been shown that a linear arrangement of vertices with crossings can achieve a smaller value of D than that of a minimum linear arrangement that minimizes D when no crossings are allowed (Hochberg and Stallmann 2003) - Fig. It has been shown that a linear arrangement of vertices with crossings can achieve a smaller value of D than that of a minimum linear arrangement that minimizes D when no crossings are allowed (Hochberg and Stallmann 2003) - Fig.…”
Section: The Relationship Between Minimization Of Crossings and Minimmentioning
confidence: 99%